Faktor-faktor yang Mempengaruhi Loyalitas Pasien di Rumah Sakit - Krishanda Rachma Setiawati; Syifaul Lailiyah (Media Gizi Kesmas, 2023)
Background: Consumer loyalty has an important role in the progress of a company, both service and goods companies. Loyal customers are an important asset for companies to win the competition in doing business. One company that must always have loyal customers is a hospital. As a company that has a health orientation, hospitals need to pay attention to things that affect patient loyalty. Objectives: this study was conducted to identify any factors related to or influencing patient loyalty in the hospital Methods: the method used is a literature review by applying the PRISMA protocol. Data sources and references are collected online through Google Scholar, SAGE, and ResearchGate. The inclusion criteria are articles published in the period 2017-2022, original research, full text, and open access. Discussion: Patient loyalty in hospitals can be influenced by several things, namely service quality factors, marketing mix factors consisting of price elements, product elements, promotional elements, process elements, and people elements, as well as patient satisfaction factors. Conclusions: Service quality, marketing mix and patient satisfaction have a significant relationship to patient loyalty in the hospital